PANCASILA SEBAGAI KONSEPSI POLITIS DAN ISI NALAR PUBLIK DALAM POLITIK HUKUM INDONESIA - Petrus CKL Bello (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Public reason is a term from John Rawl as published in his book Political Liberalism (1993) which he then discusses again in the article "The Idea of Public Reason Revisted" (1997). Rawls defines public reason as the reasoning of citizens about the nature of the constitution and issues of basic justice which originate from the most reasonable political conception of justice which presupposes the existence of an 'overlapping consensus' (slice) between reasonable comprehensive doctrines, namely comprehensive doctrines which accept constitutional-democratic government accompanied by the idea of a legitimate legal order. Pancasila is a political conception and content of public reason, which is practiced especially in public political forums, including Indonesian legal politics. However, now many people doubt the position of Pancasila as a political conception and the content of public reason because there are still many disputes about the freedom to practice religious teachings, there are still many attempts to shift Pancasila as the basis of positive law, there are still many abuses of the law by the authorities to perpetuate power and carry out other bad actions that detrimental to the people. This article attempts to explain this problem clearly while trying to find a solution.